Is There a Relationship Between Maxillary Sinus Findings and Skeletal Malocclusion? - Aksakalli, Sertac; Sen Yilmaz, Berza; Birlik, Muhammet; Dadasli, Ferit; Bolukbasi, Esra (My University, 2015)
Objective: No study has investigated the relationship between maxillary sinus findings and skeletal malocclusion based on cone-beam computed tomography (CBCT). The objectives of this study were to determine the relationship between the frequency of sinus findings and patients- skeletal malocclusion classification.